Implementasi Evaluasi Program Pendidikan Islam: Analisis Peran, Bentuk dan Kendala Kepala Sekolah - Munandar, Aris; Putri, Yulian Amanda; Marfuah, Tina Siti; Rulbadiyah, Rulbadiyah (Fitrah: Journal of Islamic Education, 2023)
Evaluation of the Islamic education program is the responsibility of the school principal, it aims to achieve the aspired educational goals. However, school principals often do not understand the role and forms of evaluation. This study aims to analyze the implementation of educational program evaluation at SD 92 Muara Kibul, focusing on three things, namely the role and constraints of school principals, as well as the form of program evaluation. The research method used is qualitative, with a narrative approach. Data collection used observation, interviews, and documentation studies. Data analysis through data collection, data reduction, data presentation, and conclusion drawing. The results revealed that the role of school principals in evaluating education programs is to design program evaluations, collect information from various sources, assess evaluation results, make improvements based on evaluation findings, involve teachers, students, and parents, build a positive attitude towards evaluation as a tool for improvement. The form of program assessment is divided into two, namely assessment according to standards and assessment based on Islamic programs. The obstacles faced are limited resources, time, lack of cooperation with external parties.